A Systematic Review and Meta-Analysis to Assess Patient-Reported Outcomes after Lung Cancer Surgery - Sayf Gazala; Jean-Sébastien Pelletier; Dale Storie; Jeffrey A. Johnson; Demetrios J. Kutsogiannis; Eric L. R. Bédard (The Scientific World Journal)
The main objective of this review was to systematically review, assess, and report on the studies that have assessed health related quality of life (HRQOL) after VATS and thoracotomy for resection of lung cancer. We performed a systematic review of six databases. The Downs and Black tool was used to assess the risk of bias. Five studies were included. In general, patients undergoing VATS have a better HRQOL when compared to thoracotomy; however, there was a high risk of bias in the included studies. The consistent use of a lung cancer specific questionnaire for measuring HRQOL after surgery is encouraged.